2018
DOI: 10.3389/fphar.2018.00779
|View full text |Cite
|
Sign up to set email alerts
|

Bone Protective Effects of Danggui Buxue Tang Alone and in Combination With Tamoxifen or Raloxifene in vivo and in vitro

Abstract: Danggui Buxue Tang (DBT), a traditional Chinese Medicine decoction containing Astragali Radix (AR) and Angelicae Sinensis Radix (ASR), is commonly prescribed for women in China as a remedy for menopausal symptoms. Previous study indicated that DBT stimulated cell growth and differentiation of human osteosarcoma MG-63 cells and exhibited estrogenic properties via estrogen receptors (ERs). The present study aimed to study the bone protective effects of DBT and its potential interactions with selective estrogen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…As expected, EXD and SERMs was effective in attenuating bone loss at three bone sites regarding BMD and bone microarchitecture in mature ovariectomized rats. EXD and SERMs could restore the serum OCN level, a speci c osteoblast product, and is considered a biomarker for bone formation [15] while only SERMs could restore urinary DPD level, a breakdown product of collagen during bone resorption and is a biomarker for bone resorption in OVX rats [13]. Afterward, we demonstrated that EXD could interact with SERMs to exert bone protection.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As expected, EXD and SERMs was effective in attenuating bone loss at three bone sites regarding BMD and bone microarchitecture in mature ovariectomized rats. EXD and SERMs could restore the serum OCN level, a speci c osteoblast product, and is considered a biomarker for bone formation [15] while only SERMs could restore urinary DPD level, a breakdown product of collagen during bone resorption and is a biomarker for bone resorption in OVX rats [13]. Afterward, we demonstrated that EXD could interact with SERMs to exert bone protection.…”
Section: Discussionmentioning
confidence: 73%
“…The dose of EXD, tamoxifen and raloxifene used in the present was selected based on our previous study and converted from its clinical dosages [11], while dosages of tamoxifen and raloxifene used in the present study were chosen based on our previous study in OVX rats [13], which are equivalent to 11 mg/kg.day and 33.3 mg/kg.day in human, respectively. These dosages are close to the clinical dosages of them (10-40 mg/kg.day of tamoxifen for breast cancer treatment, 60mg/kg.day of raloxifene for treatment and prevention of osteoporosis as well as prevention for breast cancer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone properties of the trabecular bone at the proximal tibia and distal femur as well as lumbar vertebra were determined by micro-CT (μCT40, Scanco Medical, Switzerland) as previously described ( Zhou et al, 2018 ). The source energy selected for this study was 70 KVp and 114 μA with a resolution of 21 μm.…”
Section: Methodsmentioning
confidence: 99%
“…TCM has been used in China for thousands of years, and it exerts a beneficial therapeutic effect and reduces side effects through multiple herb combinations to prevent and treat various diseases [ 12 ]. Meanwhile, TCM has increasingly been found to be effective in the treatment of osteoporosis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%